QUEUE SYSTEMS ANALYSIS AND PENSIMULASIAN AT AIRPORT SOEKARNO HATTA - Dwi Indriati; Sahni Damerianta, Skom, MMSI Sahni Damerianta, Skom, MMSI (Jurnal Sistem Informasi, 2006)
Currently queuing theory is applied in many areas of business, industry, transport andeveryday problem the other. A queue can occur if the arrival rate is greater than thelevel of service. In theory there are two queue model queue is a queue model ofsingle-channel and multi-channel queuing model. In single-channel queuing modelthere is only one service facility, while in multi-channel queue more than one servicefacility.Both models are applied to the case of queuing system at Soekarno Hatta Airport todetermine the operating characteristics of queuing systems by using simulationtechniques or formulas queue. Where is the solution obtained will be compared todetermine the level of service efficiency. In this study we concluded that thesettlement system operating characteristics of multi-channel queuing model with thesimulation technique is more complicated but more efficient.